Advances in Interdisciplinary Engineering Select Proceedings of FLAME 2018 - Kumar, Mukul; Pandey, R. K.; Kumar, Vikas; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents select proceedings of the International Conference on Future Learning Aspects of Mechanical Engineering (FLAME 2018). The book discusses interdisciplinary areas such as automobile engineering, mechatronics, applied and structural mechanics, bio-mechanics, biomedical instrumentation, ergonomics, biodynamic modeling, nuclear engineering, agriculture engineering, and farm machineries. The contents of the book will benefit both researchers and professionals. .
Nox Emission Reduction in Diesel Engine Through Developed Cooled Egr Setup -- Study of Enablers And Attributes for Effective Scm of Fmeg: A Review -- Impact Strength of Silver Date Palm Leaf Reinforced Polyester Composites -- Cfd Modeling of Commercial Slurry Flow Through Horizontal Pipeline -- Performance And Emission Analysis of A C.I. Engine Using Ethanol And Its Blends With Jojoba Biodiesel And Diesel As A Fuel -- Simulation & Modelling of Solar Trough Collector -- Effect of Oxygen Enrichment on The Performance of A Rotary Furnace: A Harbinger To Ecological Sustenance And Pollution Free Castings -- A Neural Network Based Comparative Analysis of Br, Lm And Scg Algorithms for Detection of Particulate Matter -- Theoretical Study of Solar Air Heater Using Matlab -- Decision Making for Selection of Most Suitable Materials for Biomedical Applications.
Keywords: Mechanical engineering; Mechatronics; Biomedical engineering; Nuclear engineering; Mechanical Engineering; Mechatronics; Biomedical Engineering and Bioengineering; Nuclear Energy